2020
DOI: 10.1111/and.13930
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of esculetin against aluminium chloride‐induced reproductive toxicity in rats

Abstract: The metals are ubiquitous in nature and they have a wide range of uses in industry. They remain in nature for a long time and it is very difficult for mankind to protect himself from metal exposure (Pizent et al., 2012). Aluminium is one of the most common elements in the earth's crust and takes only the value of +3 (Mayyas et al., 2005). It becomes inevitable for people to be exposed to Aluminium because of their presence in dust particles in the air, food additives, phosphate binders, antacids, buffered anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…[55,56] Previous research has found esculetin to have anti-inflammatory properties. [37,57] These anti-inflammatory properties of esculetin are thought to be due to its antioxidant properties, which suppress inflammatory cell activation and migration by increasing defense against lipid peroxidation.…”
Section: Histopathological Resultsmentioning
confidence: 99%
“…[55,56] Previous research has found esculetin to have anti-inflammatory properties. [37,57] These anti-inflammatory properties of esculetin are thought to be due to its antioxidant properties, which suppress inflammatory cell activation and migration by increasing defense against lipid peroxidation.…”
Section: Histopathological Resultsmentioning
confidence: 99%
“…Consumption of water with a high aluminum content caused a decrease in cognitive and blood functions but had no effect on the kidneys of Bangka Island residents, in Indonesia (Irfannuddin et al, 2019). Al is also found in dust particles, food additives, antacids, buffered analgesics, antiperspirants, cooking vessels, tinned boxes, infant formulas, cosmetics, mining, drinking water, and several herbal preparations (Angelova et al, 2019; Türk et al, 2021), manufacturing, food, composed of kitchen utensils, medicines, cosmetics, food additives (Kumar et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Metals are ubiquitous and have multiple industrial uses [1]. They persist in nature for long, making it difficult for humans to avoid metal exposure [2].…”
Section: Introductionmentioning
confidence: 99%
“…They persist in nature for long, making it difficult for humans to avoid metal exposure [2]. Aluminum is found in airborne dust particles, food additives, phosphate binders, antacids, buffered analgesics, antiperspirants, cooking vessels, tinned boxes, infant formulas, cosmetics, mining, drinking water, and several herbal preparations [1,3]. For example, aluminum chloride (AlCl 3 ) is present in many manufactured consumables and is considered a toxic element [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation